Genetic testing to gain diagnostic clarity in neurofibromatosis type 2 and schwannomatosis. Issue 8 (31st May 2022) - Burns, Rebecca; Niendorf, Kristin; Steinberg, Kathleen; Mueller, Amy; Ly, Ina; Jordan, Justin T.; Plotkin, Scott R.; Hicks, Stephanie R.
Abstract: Neurofibromatosis type 2 (NF2) and schwannomatosis (SWN) have distinct genetic etiologies but overlapping phenotypes. Genetic testing may be required for accurate diagnosis, which is critical for determining prognosis, screening recommendations, and treatment options. Our study aimed to compare the efficacy of germline‐only versus paired (germline and tumor) genetic testing for clarifying the diagnosis in patients with features of NF2 and SWN. We performed a retrospective chart review of patients referred for NF2/SWN genetic testing at Massachusetts General Hospital from 2015 to 2020. Logistic regression analysis was performed to assess factors associated with diagnostic clarity. Overall, paired testing had 8.5 times greater odds of providing diagnostic clarity than germline‐only testing ( p  < 0.01). Among patients who underwent paired testing, those who had analysis of two or more tumors had the greatest likelihood of gaining diagnostic clarity, with odds 13 times greater than patients who underwent germline‐only testing ( p  < 0.01). Paired testing with analysis of one tumor significantly increased the odds of diagnostic clarity over germline‐only testing by a factor of 6.5 ( p  < 0.01). These results have implications for genetic testing strategies and counseling patients about genetic testing utility. They also support the routine use of testing in individuals with suspected NF2 or SWN and improved insurance coverage for paired testing within this population.